Glycosylation-independent functions for distinct glypican core proteins drive cell-specific responses in corticogenesis - Sara Douceau; Tanya Deutsch Guerrero; Chloé Borowski; Chloé Lourenço; Margot Weber; Hanna Kavaliova; Emma Brault; Camille Pons; Anne Roumier; Rebekka Wild; Julien Ferent (Proceedings of the National Academy of Sciences, 2026)
The extracellular matrix plays critical roles in orchestrating cell communication and behaviors in response to various extracellular signals. It is a complex network composed of proteins and polysaccharides, whose individual and synergistic roles in cellular signaling, structural integrity, and tissue homeostasis remain active areas of investigation. Here, we find that in the developing cerebral cortex, distinct glypicans, which are heparan sulfate proteoglycans, present very precise and complementary expression patterns. More precisely, GPC4, which is expressed in cortical progenitors, promotes their proliferation and the generation of intermediate progenitors, whereas neuronal GPC2 acts as a brake on radial neuronal migration. The diverse biological functions of these proteoglycans are widely regarded as being intrinsically tied to their glycosaminoglycan (GAG) chains. Strikingly, we found that these effects are mediated only through glypican core proteins, rather than their heparan sulfate glycosylations. We found that the only difference between them is in their C-terminal disordered regions, which have a high density of charged residues. GPC2 is strongly basic, whereas GPC4 is acidic. Together, our findings highlight how specific proteoglycan protein cores are required to drive sequential cellular responses during cortical development in a glycosylation independent manner.